THE HISTORY OF WORLD MUSIC ART WITHIN THE CONTEXT OF RELATIONSHIP BETWEEN THE EMOTIONAL AND THE RATIONAL - Rakityanska Liudmyla (Borys Grinchenko Kyiv Metropolitan University, 2021)
The article presents the results of the analysis of musical art history in the context of the relationship between its emotional and rational constituents. The author traces the overall evolution of the world music, which in itself is a process of a complex dialectical relationship of the emotional and the rational, and which has been conditioned by the dominant philosophical worldview of a specific historical epoch, that determined the variability of artistic priorities, their emotional and intellectual balance or otherwise demarcating them by the dominating rational-mediated or emotional-sensory constituent. The research has established that the primitive culture is characterized by a syncretism of mythological and ideological ideas of the primitive human, which was reflected in the folk tradition; in the era of Ancient art, the Greek philosophers gave preference to reason while comprehending art, which went in line with the rational, philosophical and ideological orientation of the society at that time; in the Middle Ages era, this tendency fixed itself in the theological-rationalist search of the «fathers of the church», which was reflected in various genres of church music, that was religious, ascetically oriented, strictly regulated, as well as emotionally limited; the musical art of the Renaissance with its faith in the unlimited possibilities of harmonious human development is characterized by the unity and balance of the emotional and the intellectual; the New Age art was marked by new artistic trends, including Baroque and Classicism. The Baroque concept of musical art was consonant with the Renaissance tradition in terms of defining the main purpose of art as the need to reflect the sensuality of the real world; the art of the Classicism is subject to strict regulations, appealing to the human mind, instead of the senses, it is based on «rationalism», the prevailing philosophical worldview at the time; a harmonious combination of both emotional and personal experiences together with a deep intellectual comprehension of life is the leading feature of the art of the Romantic era; the modern music culture demonstrates the tendency to strengthen the rational constituent.